Phase 1b Trial of Ficlatuzumab, a Humanized Hepatocyte Growth Factor Inhibitory Monoclonal Antibody, in Combination With Gefitinib in Asian Patients With NSCLC - Tan, Eng-Huat (WILEY, 2022)
10.1002/cpdd.427